Pengaruh Promosi Penjualan dan Harga Terhadap Keputusan Pembelian Pada Brand Mixue di Surabaya Selatan - Muhammad Khalid Alfarisi; Iswati I; Anis Fitriyasari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the influence of sales and price promotions on the purchase decision of the South Surabaya Mixue brand.Along with the development of technology and communication, as well as the development of the economic field in the current era, of course economic actors or corporate companies in Indonesia must be able to build and add a wider marketing space for business actors to develop their businesses. With the entry of foreign culture in the era of globalization, so that entrepreneurs in Indonesia can compete and so as not to be left behind, economic actors must be able to attract as many buyers or consumers as possible for success in doing business. This can be done by implementing an effective marketing strategy, for example in terms of promotion, and price is believed to be the most crucial aspect of the marketing mix. The purpose of promotion and pricing is aimed at being able to attract the potential to increase consumers for the company's profit. Therefore, this study aims to prove the influence of marketing activities, which in this case is promotion and pricing that are aimed at triggering significant consumer purchase decisions, especially in the fb business focused on the Mixue brand. In this study, the sample used was as many as 100 respondents who represented the public's perspective on the brand in question. The results of this study prove that marketing activities through promotion and pricing have a positive and significant effect on consumer purchase decisions